2021
DOI: 10.1093/cid/ciab048
|View full text |Cite
|
Sign up to set email alerts
|

The Infectious Diseases Society of America Guidelines on the Diagnosis of COVID-19: Molecular Diagnostic Testing (January 2021)

Abstract: Background Accurate molecular diagnostic tests are necessary for confirming a diagnosis of coronavirus disease 2019 (COVID-19). Direct detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleic acids in respiratory tract specimens informs patient, healthcare institution and public health level decision-making. The numbers of available SARS-CoV-2 nucleic acid detection tests are rapidly increasing, as is the COVID-19 diagnostic literature. Thus, the Infectious Diseases S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
193
0
21

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(223 citation statements)
references
References 170 publications
3
193
0
21
Order By: Relevance
“…However, rapid tests are typically highly specific. 5 GPA flare was considered as a cause of her illness; however, the positive SARS-CoV-2 tests and improvement without immunosuppression argue against this. Corticosteroids are a known risk factor for severe COVID-19 6 ; however, she had not taken prednisone in the approximately 4 weeks preceding initial infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, rapid tests are typically highly specific. 5 GPA flare was considered as a cause of her illness; however, the positive SARS-CoV-2 tests and improvement without immunosuppression argue against this. Corticosteroids are a known risk factor for severe COVID-19 6 ; however, she had not taken prednisone in the approximately 4 weeks preceding initial infection.…”
Section: Discussionmentioning
confidence: 99%
“…2). The Infectious Diseases Society of America Guidelines on the Diagnosis of COVID-19 currently make no recommendations for or against the use of capillary blood in serological assays due to a knowledge gap on the subject 6 . We hope that the success of our study begins to fill this knowledge gap, paving the way for further proof-of-concept studies using capillary blood.…”
Section: Discussionmentioning
confidence: 99%
“…5 Research Support Division, Occupational Health and Safety, OIST, Onna-son, Okinawa, Japan. 6 Research Support Division, Office of the Provost, OIST, Onna-son, Okinawa, Japan. 7 Institute of Biological Chemistry, Academia Sinica, Taipei, Taiwan.…”
mentioning
confidence: 99%
“…The American Association of Infectious Diseases (IDSA) recommends testing nasopharyngeal specimens instead of the oropharyngeal specimen (or saliva) due to lower sensitivity to oropharyngeal specimens and lack data on the accuracy of saliva specimens [31]. Fang et al [34] reported that among 51 patients hospitalized in China with fever or acute respiratory symptoms and ultimately a positive PCR test, the initial PCR test was negative in 15 patients (29.0%), and they were subsequently diagnosed only after repeated tests.…”
Section: Discussionmentioning
confidence: 99%